A Five-Level Unity-Gain Active Neutral-Point-Clamped Inverter Designed Using Half-Bridges - Lee, Sze Sing; Siwakoti, Yam P.; Barzegarkhoo, Reza; Lee, Kyo Beum (2022 International Power Electronics Conference, IPEC-Himeji 2022-ECCE Asia, 2022)
This paper proposes a novel 5-level active neutral-point-clamped (ANPC) inverter that doubles the voltage gain of the conventional topology from half to unity. Each phase of the proposed topology is constituted by three half-bridges that control a flying capacitor to generate 5 symmetrical ac voltage levels. Natural voltage balancing of dc-link and flying capacitors in the proposed topology implies that the sensors and voltage balancing controller commonly used in the conventional ANPC inverter is no longer necessary. In addition to switch count reduction, the most noteworthy merit of the proposed topology is its ease of implementation with commercial half-bridge modules, where the design of dedicated circuit is not needed. The operation of the proposed 5-level unity-gain ANPC (5L-VG-ANPC) inverter is analyzed and validated through simulation and experimental tests.
Keywords: 5-level; Active neutral point clamped; Active neutral-point-clamped inverte; Flying capacitor; Half-bridge; Multi Level Inverter (MLI); Neutral-point clamped inverters; Unity gain; Voltage balancing; Voltage gain; 5-level; ANPC inverter; half-bridge; multilevel inverter; unity-gain